Oscillation criteria in neutral equations of n order with variable coefficients. (1991) - Georgiou, D. A.; Qian, C.
Abstract : Consider then -order neutral delay differential equationd n d t n [ y ( t ) + P ( t ) y ( t − τ ) ] + Q ( t ) y ( t − σ ) = 0 whereP, Q ∈ C [ [ t 0, ∞ ), ℝ ] and the delaysτ andσ are nonnegative real numbers. In this paper we examined the oscillatory behavior of the solutions of the above equation using techniques which allow the relaxation of the restrictions which has been introduced previously. We illustrate new type of conditions which improve and extend known results, by relaxing hypotheses thatP is constant andQ isτ -periodic.